Interior temperature dynamics and its implications for heatstroke risk: Designing an IoT-based vehicular heatstroke sensor device - Mokhtar, Nur Hazwani; Ramli, Mizah; Azmi, Nur Fatihah; Paiman, Noor Faradila; Mohd Jawi, Zulhaidi (Semarak Ilmu Publishing, 2024)
Vehicular heatstroke incidents involving children represent a critical issue with potentially severe consequences. To address this problem, this research presents an IoT-based Child Safety System (CSS) designed to prevent and mitigate heatstroke incidents in vehicles. This article focuses on the development and evaluation of the system, taking a user-centric approach to ensure its effectiveness and user acceptance. The study begins with a comprehensive survey conducted to gather user requirements and preferences regarding CSSs. The survey data provides valuable insights into the design and functionality expectations of potential system users, enabling the development of a solution that aligns with their needs. Subsequently, an experiment is conducted to evaluate the performance of the proposed IoT-based CSS. The experiment involves the installation of temperature sensors in a fleet of vehicles, with data collected to monitor and analyze the temperature variations inside the vehicles during different conditions. Consequently, the acquired temperature data assesses the system’s ability to detect potentially dangerous situations and provide timely alerts to caregivers. Preliminary results indicate a positive response from the survey participants, with a high level of interest in and willingness to adopt the IoT-based CSS. Moreover, the temperature data collected during the experiment demonstrates the system’s capability to effectively monitor the in-vehicle temperature and promptly notify caregivers when potentially hazardous conditions arise. This article presents a preliminary investigation, laying the foundation for further research and development in the field of CSSs. Future studies could focus on refining the system’s design, incorporating additional features to enhance its functionality, and conducting larger-scale trials to evaluate its effectiveness in real-world scenarios. Overall, this research contributes to the ongoing efforts to combat vehicular heatstroke incidents involving children. By emphasizing a user-centric approach and leveraging IoT technology, the proposed CSS shows promising potential in preventing tragic incidents and safeguarding the well-being of children in vehicles.